Efficacy of Gooseberry, Tomato and Red Grapes Powder as Preservative in Restructured Chicken Block - Najeeb, A.P.; Mandal, P. K.; Pal, U. K. (Journal of Meat Science, 2015)
Use of natural preservatives to increase the shelf-life of meat products is promising because extracts or powders of many herbs, plants, vegetables and fruits have antioxidant and antimicrobial properties. Hence, the present study was planned to find out the effect of powders of red grapes, gooseberry and tomato on the quality and shelf life of restructured chicken block under refrigerated storage (7±1°C). Incorporation of powders at 1% level did not show any significantly effect on cooking yield (%) and proximate composition. A significantly (P<0.01) lower pH value was recorded for gooseberry powder added products. All the products added with fruit powders and BHT had significantly (P<0.01) lower thiobarbituric acid (TBA) values than control. Gooseberry added products were recorded to have significantly (P<0.01) lower TBA values on 14th, 17th and 20th day of storage. The free fatty acid (FFA) values were recorded to be significantly (P<0.01) lower in gooseberry added products compared to control products throughout the period of storage.